EFEKTIVITAS ANTIBAKTERI NANO KITOSAN TERHADAP PERTUMBUHAN Staphylococcus aureus (in vitro) - Ade Komariah (Universitas Sebelas Maret, 2014)
Abstract- Mouth is considered as a not homogeneous environment. These following aspects may caused a significant contribution towards the cause of infection namely; the mucosal surfaces in the mouth and teeth are not the same, has warm temperatures, moisture and nutrient-rich environment which increasing the growth of microorganisms. Staphylococcus aureus can trigger the occurrence of infectious diseases, which is acute apical abscess. Nano chitosan is a physical modification of chitosan which posses antibacterial capability. The purpose of this study to test the effectiveness of antibacterial nano chitosan in different degree of deacetylation and concentrations against Staphylococcus aureus. This experimental study was conducted with disc’s method and using some concentration of 90%, 45%, 22,5%, 11,25%, 5,625%, 2,812%, 1,406%, 0,703%, 0,351%, 0,175% and 2 control groups, namely positive and negative controls. The statistical analysis using Chi - Square manually. The test results of antibacterial activity against S. aureus is the Minimum Inhibitory concentration (MIC) of nano chitosan DD 89% and 93% at a concentration of 22.55%. Minimum Bactericidal Concentration (MBC) nano chitosan DD 89% is at a concentration of 45% , while the nano chitosan DD 93% at a concentration of 22.5% . The results of statistical tests showed there are differences of MIC and MBC at different concentrations but there is no difference on different the degree of deacetylation test. Keywords: Antibacterial, Nano chitosan, S.aureus, MIC, MBC